PENGARUH KOMUNIKASI ORGANISASI TERHADAP MOTIVASI DAN KEPUASAN KERJA ANGGOTA POLISI - Tugimin Supriyadi; Bagas Seno Aji, Firanti Dhiva Kirana, M. Akbar, Naufal Zaidan, Puspa Lusiana (Adisam Publisher, 2024)
This research discusses the importance of job satisfaction in human resource management, especially in the context of the Indonesian National Police. The police, as an institution that plays a vital role in the rule of law, faces various obstacles regarding personnel, equipment and operational budgets. Therefore, community participation and effective communication strategies are key in building safety and security. Job satisfaction influences the positive and negative behavior of police officers, and is related to workers' happiness, psychological health and quality of life. This research uses a literature study method by analyzing 10 journals regarding the influence of organizational communication on the motivation and job satisfaction of police officers. The research results show that promotion and motivation have a positive and significant effect on job satisfaction. Good job satisfaction has the potential to improve performance, which ultimately supports the achievement of police organizational goals. Thus, effective communication strategies and a flexible approach according to situations and conditions are very necessary in police organizations to achieve the desired goals.